Cows in the city: How consumer demands sustain urban dairying in the IT capital of India - Neda Yousefian; Shahin Alam; Kumsher Basavarajappa Ramappa; Eva Schlecht; Christoph Dittrich (Urban Agriculture & Regional Food Systems)
Abstract Spurred by rising incomes and urbanization, the “nutrition transition” in India has led to many dietary changes, including an increase in per capita milk consumption, which has quadrupled since 1970. We examine how changing preferences for milk are shaping consumer demand and the rise in dairy consumption. We focus on urban dairying and milk alternative food networks (AFNs), in which farmers sell directly to consumers. To better understand milk AFNs, we interviewed consumers (n = 95) and dairy farmers (n = 62) in urban (within 15 km) and peri‐urban (15–30 km) areas of the south Indian megacity Bengaluru. Consumers were grouped by location and the type of milk they purchase. Dairy farmers were grouped based on their farm distance to the city center and the breed of cattle they rear: indigenous (Bos indicus) or crossbred (Bos indicus × Bos taurus). We found that demand for farm‐fresh milk is driven by concerns for freshness, quality, and health. In our sample, urban dairy farmers are producing more milk and more frequently cite dairying as their sole or primary source of income compared to peri‐urban farmers. The role of milk AFNs is thus two‐fold: they allow consumers to know the origins of their milk, and they provide a marketing channel for farmers in the absence of urban dairy cooperatives. While urbanization tends to push dairying to peri‐urban and rural areas, the consumer demand for farm‐fresh milk, as well as the cultural and religious significance of the cow in India, is prolonging their presence in Indian cities.